FEATURES OF INTRAYEAR-DISTRIBUTION OF PRECIPITATION ON THE TERRITORY OF THE ARARAT VALLEY (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Features of intrayear-distribution of precipitation in Ararat Valley, an important natural and economic region of the republic, are studied and evaluated. Issues of intrayear-distribution of precipitation are discussed and studied as a monthly, and seasonal and annual basis. Taking into account the climatic characteristics of the region and the practical value of precipitation, allocated as warm or vegetation (IV–X ), hot (VII–VIII) and cold (XI–III), as well as the high-water periods.
Keywords: atmospheric precipitation; intrayear-distribution; height of area; vertical gradient; correlation relationship; Ararat Valley